Women in Electrochemistry- Contributions, Challenges and Potential Solutions. Issue 1 (14th January 2022) - Das, Ananya; Nagaraj, Pratham; Bhat Panemangalore, Devadas
Abstract : The perspectives gained over the years by women working in electrochemistry are described in order to throw light on their history and current status and achievements in this field, the potential that the future holds, and the role that well-established female electrochemists and the electrochemical societies can play in improving upon the under-representation and under-recognition of women in electrochemistry. Here, a hopeful and optimistic future is presented, in which men and women, both equally contribute to this field, which encompasses our entire life, from corrosion and life of materials to transportation industry.